Urban–Rural Disparities in the Lung Cancer Surgical Treatment Pathway: The Paradox of a Rich, Small Region - Minerva, Eleonora Maddalena; Tessitore, Adele; Cafarotti, Stefano; Patella, Miriam (Frontiers in Surgery, 2022)
Rural population in large Countries often receive delayed and/or less effective diagnosis and treatment for lung cancer. Differences are related to population-based factors as lower pro capita income, increased risk factors, or to differences in access to facilities. Switzerland is a small, rich Country with peculiar geographic and urban characteristics. We explored the relationship between lung cancer diagnostic-surgical pathway and urban-rural residency in our region. We retrospectively analyzed the medical records of 280 consecutive patients treated for primary lung cancer at our institution (2017-2021). This is a regional tertiary center for diagnosis and treatment, and data were extracted from a prospectively collected clinical database. We included anatomical lung resection. Collected variables included patients and surgical characteristics, risk factors, comorbidities, histology and staging, symptoms (vs incidental diagnosis), general practitioner (GP) involvement, health insurance, suspected test-treatment interval. The exposure was rurality, defined by the2009 rural-urban residency classification from the Land Department. 150 patients (54%) lived in rural areas. Rural patients had higher rate of smoking history (93% vs 82%; p=0.007). Symptomatic vs incidental diagnosis did not differ as well as previous cancer rate, insurance and pathological staging. In rural patients, there was greater burden of comorbidities (mean Charlson Comorbity Index Age-Adjusted 5.3 in rural population vs 4.8 in urban population, p=0.05) and GP was more involved in diagnostic pathway (51% vs 39%, p=0.04). Interval between first suspected test and treatment was significantly shorter (56 vs 66.5 days, p=0.03). A multiple linear regression with backward elimination was run. These variables statistically predicted the time from first suspected test and surgical treatment, [F(3, 270), p<0.05, R2=0.24]: rurality (p= 0.04), GP involvement (p= 0.04) and presence of lung cancer-related symptoms (p=0.02). In our territory with inhomogeneous population distribution and geographic barriers, residency has an impact on lung cancer pathway. It seems paradoxical that rural patients had a shorter route. More constant involvement of GP might explain this finding having suggested more tests for high-risk patients in absence of symptoms or follow-ups. This did not change staging of surgical patients, but it might be essential for the organization of effective lung cancer screening programs.